A Positive Tinel Sign as Predictor of Pain Relief or Sensory Recovery after Decompression of Chronic Tibial Nerve Compression in Patients with Diabetic Neuropathy - Dellon, A. Lee; Muse, Vicki L.; Scott, Nickerson D.; null (Journal of Reconstructive Microsurgery, 2012)
Predictive ability of a positive Tinel sign over the tibial nerve in the tarsal was evaluated as a prognostic sign in determining sensory outcomes after distal tibial neurolysis in diabetics with chronic nerve compression at this location. Outcomes were evaluated with a visual analog score (VAS) for pain and measurements of the cutaneous pressure threshold/two-point discrimination. A multicenter prospective study enrolled 628 patients who had a positive Tinel sign. Of these patients, 465 (74%) had VAS >5. Each patient had a release of the tarsal tunnel and a neurolysis of the medial and lateral plantar and calcaneal tunnels. Subsequent, contralateral, identical surgery was done in 211 of the patients (152 of which had a VAS >5). Mean VAS score decreased from 8.5 to 2.0 (p <0.001) at 6 months, and remained at this level for 3.5 years. Sensibility improved from a loss of protective sensation to recovery of some two-point discrimination during this same time period. It is concluded that a positive Tinel sign over the tibial nerve at the tarsal tunnel in a diabetic patient with chronic nerve compression at this location predicts significant relief of pain and improvement in plantar sensibility.
Keywords: Tinel sign; diabetic neuropathy; neurolysis